Plant age on fruit quality of three orange cultivars - Carvalho, Vânia Dêa de; Chitarra, Maria Isabel Fernandes; Chitarra, Adimilson Bosco; Morais, Augusto Ramalho de (Pesquisa Agropecuaria Brasileira, 2014)
Data on orange fruits (Citrus sinensis (L) Osbeck) taken during three successive years from Pera Rio, Natal and Valência cultivars (six, seven and eight Years old trees), showed differences on fruit composition with the advance of age. The following observations were made: size, weight, pH, soluble solids, titrable acidity, reducing and non-reducing sugars and total carotenoids. The fruits from eight years old trees presented the highest degree of quality. The Valência fruits had the best physical characteristics but the highest sugar content was present on fruits of Natal and Pera cultivars.
Keywords: fruit composition